(untitled) (Bangladesh Medical Journal Khulna, 2014)
Agenesis of the uterine cervix is uncommon uterine anomaly. We report a case of 22 year old woman who was admitted in a private hospital with menouria and pelvic mass. Examination found no communication between vagina and uterus. Cervix was absent. Utero-vaginal anastomosis was done and a Foleys catheter was inserted in the uterine cavity for 14 days. During follow up of 1 month and 6 month after surgery patient was menstruating normally and examination revealed that the communication between the uterus and vagina was healed and had been sexually active at 6 months after the procedure. So uterovaginal anastomosis can be safely done in cervical agenesis. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18237 Bang Med J (Khulna) 2013; 46 : 28-30